2004
DOI: 10.23869/bphjbr.10.1.200410
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH INFUS RIMPANG TEMULAWAK (Curcuma xanthorrhiza) TERHADAP KADAR HEMOGLOBIN DAN JUMLAH ERITROSIT TIKUS PUTIH YANG DIBERI LARUTAN TIMBAL NITRAT [(PbNO3)2]

Abstract: The purpose of this experiment was to study the effect of turmeric (Curcuma xanthorrhiza) rhizome infuse to hemoglobin concentration and number of erythrocyte of (PbNO3)2 treated rats. Pb was presumed to be link at sulphyhydril groups that may caused an inhibition to several enzymatic process, such as d-ALAD and heme sintetase which is caused the inhibits of Hb synthesis and erythropoesis. Twenty female rats was used in this experiment. They were divided into five groups, i.e. (A) control (treated with 1 ml aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…19 The results of this study are also in line with the previous studies, which indicated that there was a significant effect of temulawak extract on breast milk production and prolactin levels. 8,9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The results of this study are also in line with the previous studies, which indicated that there was a significant effect of temulawak extract on breast milk production and prolactin levels. 8,9…”
Section: Discussionmentioning
confidence: 99%
“…8 There was an influence of temulawak consumption by postpartum mother to the smoothness of milk production. 9 Curcuma xanthorhiza Roxb contains lipid elements and hormonal structures in which these active compounds play an active role in the milk production process as they exhibit the lactagagum effect. 10 In addition, it contains polyphenols, which also play a role in increasing prolactin levels.…”
Section: Introductionmentioning
confidence: 99%